2007
DOI: 10.1152/ajpheart.01016.2006
|View full text |Cite
|
Sign up to set email alerts
|

Acute intermittent hypoxia activates myocardial cell survival signaling

Abstract: Intermittent hypoxia (IH) with repeated episodes of hypoxia-normoxia cycle has been shown to exert preconditioning-like cardioprotective effects. To understand the mechanism of these events, we investigated the changes in cardiac gene expression in response to acute IH. Mice were subjected to five cycles of 2 min of 10% O(2) plus 2 min of 21% O(2). RNA was isolated, and gene array analysis was performed. Results show that the expression of antiapoptotic genes, such as Bcl-2 and Bcl-x(L), were increased after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…These cells induce specific genes involved in oxygen homeostasis after the mediation of hypoxia-inducible factor (HIF-1␣), in turn upregulating vascular endothelial growth factor (VEGF), which are strongly activated after intermittent hypoxia (Yuan et al, 2005). Consistent with the results of other studies that used distinct protocols of intermittent hypoxia (Tin'kov and Aksenov, 2002;Park et al, 2007), our findings support the clinical use of IHH for myocardial recovery, since this protocol improves oxygen delivery to myocardium fibers. Our results give support to previous reports by E. Marticorena, in Peru, who originally described a procedure for cardiac recovery.…”
Section: Panisello Et Alsupporting
confidence: 86%
“…These cells induce specific genes involved in oxygen homeostasis after the mediation of hypoxia-inducible factor (HIF-1␣), in turn upregulating vascular endothelial growth factor (VEGF), which are strongly activated after intermittent hypoxia (Yuan et al, 2005). Consistent with the results of other studies that used distinct protocols of intermittent hypoxia (Tin'kov and Aksenov, 2002;Park et al, 2007), our findings support the clinical use of IHH for myocardial recovery, since this protocol improves oxygen delivery to myocardium fibers. Our results give support to previous reports by E. Marticorena, in Peru, who originally described a procedure for cardiac recovery.…”
Section: Panisello Et Alsupporting
confidence: 86%
“…With respect to cellular signaling pathways, a recent report demonstrated that GATA-4-regulated microRNAs confer a cardiomyocyte-protective effect accompanied by activation of COX-2-prostaglandin signaling pathways [24]. An earlier report demonstrated that GATA-4 mRNA and activity in the hearts of mice were increased from 0.5 h after IPC [25]; in that study, the time course of GATA-4 expression was comparable to that in this study. Taken together, these data suggest that induction of GATA-4 by nicorandil would be a first step in the induction of COX-2 in the left ventricle.…”
Section: Discussionsupporting
confidence: 81%
“…While treatment with acute IH exerted cardioprotective effects, treating mice with a prolonged period of IH induced increased susceptibility of the heart, which was mediated by increased oxidative stress. Additional treatment with prolonged IH reversed the added myocardial damage [113,114]. It is therefore of utmost importance to delineate the complex effects of IH on the GATA family of transcription factors in the human heart.…”
Section: Gatamentioning
confidence: 99%